A service improvement report of blood-borne virus screening in a high secure mental hospital. Issue 4 (July 2019) - Strazds, Pixy; Abdelrazek, Tarek
Background: Patients in a high secure hospital are a high-risk population for exposure to blood-borne viruses (BBV) because of previous lifestyles. Objective: This service improvement study intends to improve patients care by the Infection Prevention and Control Team (IPCT) coordinating the BBV screening and vaccination programme within the hospital. Methods: A retrospective review of patients' notes in 2007 and 2016 was used. Results: The results show an increase in screening offered and screening undertaken from 2007 to 2016. It also identifies an increase in hepatitis B vaccination programmes completed. Discussion: The expansion of the IPC and Physical Healthcare Team appear to be associated with the increase of screening and vaccination rates.